Peran Terapi Musik terhadap Penyelesaian Matematis pada Anak dengan Simptom Gangguan Konsentrasi - Al Thuba Septa Priyanggasari (Jurnal Psikologi Tabularasa, 2015)
Studies about the role of music therapy to the completion of mathematical questions on three subjects (N=3), children with attention deficit symptoms were placed at psychology service center for children with special need, at Malang. Music therapy was applied, where the children is only listening to the music without any activities in 10 minutes. The aim of music therapy are to condition the children in order to be more calm and ready to accept the lesson well. Data collection used were within-subject design. Data analyzed used a chi square for one sample test. The result showed that there were effect of music therapy to the completion of mathematical questions on children with attention deficit symptoms. The accuracy effect turned into two from three of the subject (p= 0,05) and the speed effect turned into two from three of the subject (p= 0,05).